Guided imagery and music therapy for anxiety in third-trimester pregnancy - Sumenah Sumenah; Osep Yasier Almunsiri; Lailatul Fadilah; Cucuk Kunang Sari (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Pregnancy is a sensitive period that brings physical and psychological changes, including anxiety. Anxiety is a normal reaction when it functions as an adaptive mechanism that helps individuals prepare for facing threats. To overcome anxiety, a combination of guided imagery and music therapy can be used as one of the non-pharmacological measures to reduce anxiety in pregnant women in the third trimester. Purpose: To determine the effect of a combination of guided imagery and music therapy on the anxiety level of third-trimester pregnant women in the working area. Method: A quantitative approach with a Quasi-Experiment design, utilising a One-Group Pretest-Posttest layout without a control group. The sampling technique used was non-probability, specifically accidental sampling. Based on Roscoe's theory, the sample size was set at 10-20 individuals. Results: The results of the paired samples T-test showed a p-value of 0.001, which is less than the significance level (α = 0.05). Conclusion: There is an effect of the combination of guided imagery and music therapy on the anxiety levels of pregnant women in their third trimester in the work area. Keywords: Anxiety; Guided Imagery; Music Therapy; Pregnant Women.